CODE SWITCHING IN THE SPEECH OF THE NORTH KALIMANTAN BORDER COMMUNITY—MALAYSIA - Toba, Rostanti; Rijal, Muhammad Khairul (Universitas Islam Sumatera Utara (UISU), 2023)
The purpose of the study is to describe the forms of code-switching in the speech of border community groups in Nunukan and Malinau who use two or more languages in their daily communication and to find the factors that determine code-switching in the speech of border community groups. This research method is sociolinguistic field research employing a qualitative descriptive design. The data sources are the border community organizations of Nunukan and Malinau. The study consists of primary data in spontaneous speech from various contexts of speech events by border community groups of Nunukan and Malinau and secondary data in information, sociocultural background, and language gleaned from observations and interviews. The results of this study show that (1) the forms of code-switching in the speech of border communities of Nunukan and Malinau consist of code-switching from Bugis to Indonesian and vice versa, from Tidung to Indonesian and vice versa, from Banjarese to Indonesian and vice versa, and from Indonesian to Malay-Malay and vice versa. (2) The factors that cause code-switching in the speech of border community groups (Nunukan and Malinau) are speakers, speech partners, attendance and departure of speech participants, and variations in the topic of conversation.